TI_GERICHTE 15.2004.151 vom 6. August 2004 , Spese amministrazione immobile. Spese di massa. Anticipo spese. - TI Tribunale d'appello (2004)
Spese amministrazione immobile. Spese di massa. Anticipo spese.